Triptorelin for Fertility Preservation in Adolescents Treated With Chemotherapy for Cancer. Issue 4 (May 2018) - Meli, Mariaclaudia; Caruso-Nicoletti, Manuela; La Spina, Milena; Nigro, Luca Lo; Samperi, Piera; D'Amico, Salvatore; Bellia, Francesco; Miraglia, Vito; Licciardello, Maria; Cannata, Emanuela; Marino, Silvia; Cimino, Carla; et al.
Abstract : Background: Triptorelin, a gonadotropin releasing hormone analogue, can be administered to postpubertal female individuals with cancer who receive chemotherapy to obtain menstrual suppression and decrease the risk of hemorrhage caused by thrombocytopenia. Our goal was to assess whether triptorelin also has a protective role against the gonadotoxicity of chemotherapy. Patients and Methods: This retrospective observational study includes all postmenarchal female patients who presented to our Unit from 2000 to 2015 and received chemotherapy for cancer. They were administered depot triptorelin. We evaluated long-term ovarian function in order to detect clinical signs of ovarian damage, miscarriages, and pregnancies. Laboratory follow-up consisted in dosing serum follicle stimulating hormone, luteinizing hormone, prolactin, estradiol, and progesterone. Ultrasound of the ovaries was performed as well. Results: Of 36 evaluable patients, 9 received hematopoietic stem cell transplantation (HSCT). The remaining 27 patients maintained normal ovarian function at clinical, laboratory, and ultrasound assessment. Five of them achieved spontaneous physiological pregnancy. Four of the 9 patients who underwent HSCT developed premature ovarian failure. Conclusion: Our study suggests that gonadotropin releasing hormone-a administered during chemotherapy can prevent premature ovarian failure in patients treated without HSCT and that it is not enough to preserve the ovarian function during HSCT. Hence, a prospective randomized trial with a larger population would be recommended.